Endogenous Obesity Associated with Cushing’s Disease: A Case Report - Müge Şahin; Coşkun Ateş; Ensar Aydemir; Yasemin Aydoğan Ünsal; Soner Cander; Erdinç Ertürk; Canan Ersoy; Özen Öz Gül (Turkish Journal of Internal Medicine, 2021)
Cushing’s disease (CD) constitutes most common cases of adrenocorticotropic hormone (ACTH) dependent Cushing’s syndrome (CS). CD more often occurs in women. Recent studies indicate increasing prevalence of CD amongst the obese people. Therefore, the possibility of underlying CD should be ruled out in obese people. Inferior petrosal sinus sampling (IPSS) is an important diagnostic method for diagnosing and localizing CD cases who can’t be diagnosed by standard imaging methods. IPSS can increase the success of the surgeon's treatment with information about the location of the adenoma. Here, we present a case of a 36-year-old female patient admitted to the hospital for bariatric surgery who was diagnosed having CD localized by IPSS.